The Effect of the use of effective teaching strategies, cooperative learning to learn the most important offensive skills for student's handball - Mohammed, Nihad (Journal of Physical Education, 2016)
Through the work of researchers in teaching handball and Mhahdthma for most of Physical Education lessons process in college and inquiring of some teachers and workers in the physical education field and question experienced and competent in teaching it turned out to be common in teaching multiple skills in general method and reel hand is particularly Prince method which requires the teacher to be an architect of the resolution imposing him on the student and not affront us on this method and the reduction of its advantages, but the present era is the era of development and prosperity cognitive and educational work has to be that this development keep pace so felt researchers using the method of effective teaching strategies, cooperative learning to learn the most important skills offensive for students hand pulley to be an effective method used by the teacher in the learning skills of their students with minimal effort, and target your search: 1. Preparation of educational modules using effective teaching strategies, cooperative learning to learn the most important offensive skills for students hand reel. 2. Identify the most important offensive skills for students hand reel. 3. Recognize the effect of the educational program using effective teaching strategies, cooperative learning to learn the most important offensive skills for students hand reel. Use the researchers experimental method to fit the research problem, and identifies the research community students the second stage in the Sports College of Physical Education and Science at the University of Babylon for the academic year 2014- 2015 totaling (57) male and divided by three people (a,b,c) The sample was selected randomly Statistics totaling 40 students were divided into two groups and the most important researchers used statistical methods to address data: the Allosd arithmetic mean and standard deviation and test (t-test) of the samples and the corresponding Independent The main conclusions are: 1. The results showed learning and the evolution of the control group and the group Altjeribh offensive in basic skills for students hand reel. 2. The results showed the effectiveness of effective teaching strategy of cooperative learning in the learning and development of the best offensive in basic skills for students hand reel.